2018
DOI: 10.1002/nsg.12026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a low‐cost magneto‐inductive magnetometer with a proton magnetometer: a case study on the Galali iron ore deposit in western Iran

Abstract: A B S T R A C TThe proton magnetometers, also known as the proton precession magnetometers, are among the most widely used instruments for magnetometry surveys, owing to their high resolution which is about 0.01 nT. As the economically attractive ferromagnetic deposits generate a magnetic field anomaly which exceeds 100 nT, this resolution is not needed for detecting such large signals. The recently introduced magneto-inductive technology has led to the development of a low-cost magnetometer that can measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These tools have the potential to be leveraged in purpose-built low-cost geophysical equipment that can acquire data without exceeding the durability and budgetary constraints for many types of near-surface geophysical investigations. Examples following this low-cost instrumentation approach include direct-current (DC) resistivity (Clark et al, 2016;Ahmad et al, 2019;Sirota et al, 2021), seismic nodes (Dean et al, 2017;Soler-Llorens et al, 2019;Wilson et al, 2021), and magnetometers (Schofield et al, 2012;Shahsavani, 2018), each of which has demonstrated the possibility of acquiring data of comparable quality to commercial grade systems. While such home-grown instrumentation is neither as robust nor as likely to have fully in-built safety factors as commercial-grade instruments, it can lower the barrier-to-entry for many users, enable enthusiast, academic, or humanitarian geoscience applications, and be used to develop low-cost geophysical networks for timelapse monitoring projects.…”
Section: Introductionmentioning
confidence: 99%
“…These tools have the potential to be leveraged in purpose-built low-cost geophysical equipment that can acquire data without exceeding the durability and budgetary constraints for many types of near-surface geophysical investigations. Examples following this low-cost instrumentation approach include direct-current (DC) resistivity (Clark et al, 2016;Ahmad et al, 2019;Sirota et al, 2021), seismic nodes (Dean et al, 2017;Soler-Llorens et al, 2019;Wilson et al, 2021), and magnetometers (Schofield et al, 2012;Shahsavani, 2018), each of which has demonstrated the possibility of acquiring data of comparable quality to commercial grade systems. While such home-grown instrumentation is neither as robust nor as likely to have fully in-built safety factors as commercial-grade instruments, it can lower the barrier-to-entry for many users, enable enthusiast, academic, or humanitarian geoscience applications, and be used to develop low-cost geophysical networks for timelapse monitoring projects.…”
Section: Introductionmentioning
confidence: 99%